Dr. Fakhreddin Jamali: Pharmacist, Pharmaceutical Scientist and Mentor - N.M Davies; D. R. Brocks; S.H.M Hanafy (Frontiers Media S.A., 2018)
Dr. Fakhreddin Jamali: Pharmacist, Pharmaceutical Scientist and Mentor- Dedicated to An Academic Life and Legacy of Fame and Fortune